Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! To solve the problem where you need to find pairs [tex]\((x, y)\)[/tex] that satisfy the equations:
1. [tex]\(\frac{1}{x} + \frac{1}{y} = \frac{7}{12}\)[/tex]
2. [tex]\(xy = 12\)[/tex]
we can follow these steps:
### Step 1: Simplify the equation [tex]\(\frac{1}{x} + \frac{1}{y} = \frac{7}{12}\)[/tex]
Using the equation [tex]\(\frac{1}{x} + \frac{1}{y} = \frac{7}{12}\)[/tex], we rewrite the left side with a common denominator:
[tex]\[ \frac{y + x}{xy} = \frac{7}{12} \][/tex]
Substitute [tex]\(xy = 12\)[/tex] from the given:
[tex]\[ \frac{x + y}{12} = \frac{7}{12} \][/tex]
### Step 2: Eliminate the denominators
To eliminate the denominators, multiply both sides of the equation by 12:
[tex]\[ x + y = 7 \][/tex]
### Step 3: Form a system of equations
Now, we have two equations:
[tex]\[ x + y = 7 \][/tex]
[tex]\[ xy = 12 \][/tex]
### Step 4: Solving the system of equations
The equations [tex]\(x + y = 7\)[/tex] and [tex]\(xy = 12\)[/tex] can be solved by treating [tex]\(x\)[/tex] and [tex]\(y\)[/tex] as roots of a quadratic equation. We consider a quadratic equation of the form:
[tex]\[ t^2 - (x + y)t + xy = 0 \][/tex]
Substitute [tex]\(x + y = 7\)[/tex] and [tex]\(xy = 12\)[/tex]:
[tex]\[ t^2 - 7t + 12 = 0 \][/tex]
### Step 5: Factor the quadratic equation
To solve for [tex]\(t\)[/tex], we factorize the quadratic equation:
[tex]\[ t^2 - 7t + 12 = 0 \][/tex]
This can be factored into:
[tex]\[ (t - 3)(t - 4) = 0 \][/tex]
### Step 6: Find the roots of the equation
Set each factor equal to zero and solve for [tex]\(t\)[/tex]:
[tex]\[ t - 3 = 0 \quad \text{or} \quad t - 4 = 0 \][/tex]
[tex]\[ t = 3 \quad \text{or} \quad t = 4 \][/tex]
### Step 7: Assign the solutions to [tex]\(x\)[/tex] and [tex]\(y\)[/tex]
Thus, the pairs [tex]\((x, y)\)[/tex] that satisfy both equations are:
[tex]\[ (x, y) = (3, 4) \quad \text{or} \quad (x, y) = (4, 3) \][/tex]
So, the final solutions are:
[tex]\[ (x, y) = (3, 4) \quad \text{and} \quad (x, y) = (4, 3) \][/tex]
1. [tex]\(\frac{1}{x} + \frac{1}{y} = \frac{7}{12}\)[/tex]
2. [tex]\(xy = 12\)[/tex]
we can follow these steps:
### Step 1: Simplify the equation [tex]\(\frac{1}{x} + \frac{1}{y} = \frac{7}{12}\)[/tex]
Using the equation [tex]\(\frac{1}{x} + \frac{1}{y} = \frac{7}{12}\)[/tex], we rewrite the left side with a common denominator:
[tex]\[ \frac{y + x}{xy} = \frac{7}{12} \][/tex]
Substitute [tex]\(xy = 12\)[/tex] from the given:
[tex]\[ \frac{x + y}{12} = \frac{7}{12} \][/tex]
### Step 2: Eliminate the denominators
To eliminate the denominators, multiply both sides of the equation by 12:
[tex]\[ x + y = 7 \][/tex]
### Step 3: Form a system of equations
Now, we have two equations:
[tex]\[ x + y = 7 \][/tex]
[tex]\[ xy = 12 \][/tex]
### Step 4: Solving the system of equations
The equations [tex]\(x + y = 7\)[/tex] and [tex]\(xy = 12\)[/tex] can be solved by treating [tex]\(x\)[/tex] and [tex]\(y\)[/tex] as roots of a quadratic equation. We consider a quadratic equation of the form:
[tex]\[ t^2 - (x + y)t + xy = 0 \][/tex]
Substitute [tex]\(x + y = 7\)[/tex] and [tex]\(xy = 12\)[/tex]:
[tex]\[ t^2 - 7t + 12 = 0 \][/tex]
### Step 5: Factor the quadratic equation
To solve for [tex]\(t\)[/tex], we factorize the quadratic equation:
[tex]\[ t^2 - 7t + 12 = 0 \][/tex]
This can be factored into:
[tex]\[ (t - 3)(t - 4) = 0 \][/tex]
### Step 6: Find the roots of the equation
Set each factor equal to zero and solve for [tex]\(t\)[/tex]:
[tex]\[ t - 3 = 0 \quad \text{or} \quad t - 4 = 0 \][/tex]
[tex]\[ t = 3 \quad \text{or} \quad t = 4 \][/tex]
### Step 7: Assign the solutions to [tex]\(x\)[/tex] and [tex]\(y\)[/tex]
Thus, the pairs [tex]\((x, y)\)[/tex] that satisfy both equations are:
[tex]\[ (x, y) = (3, 4) \quad \text{or} \quad (x, y) = (4, 3) \][/tex]
So, the final solutions are:
[tex]\[ (x, y) = (3, 4) \quad \text{and} \quad (x, y) = (4, 3) \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.